Identifying Predictors of Emergency Readmission Within 7 Days of Hospital Discharge: A Prospective Cohort Study - Radiyah, Eisha Tir; Khan, Abdus Salam; Imtiaz, Rabia; Tariq, Rida; Ali, Fatima (Biological and Clinical Sciences Research Journal, 2025)
Early return visits to the emergency department after discharge reflect gaps in transitional care and are associated with increased morbidity, healthcare burden, and costs. Objective: To determine the frequency of emergency department revisits within seven days of discharge and to identify associated clinical and demographic risk factors. Methods: A descriptive study was conducted at the Department of Medicine, Shifa International Hospital, Islamabad, from 5 November 2024 to 5 March 2025. A total of 275 patients discharged from the emergency department were enrolled using consecutive sampling. Patients aged 16 to 85 years, both sexes, were included. Data on demographic characteristics, comorbidities, length of hospital stay, and discharge clinical parameters were collected. Early readmission was defined as a return to the emergency department within seven days of discharge. Evaluated factors included advanced age, prolonged hospitalization, chronic illnesses, fever, tachycardia, anemia, hyponatremia, cognitive impairment, and malnutrition. Data were analyzed using SPSS version 26, with statistical significance set at p≤0.05. Results: Early readmission occurred in 26.2% of patients. Among readmitted individuals, 56.9% were aged 60 or older. Significant associations were observed with hypertension (p=0.001) and cognitive impairment (p<0.001). Nutritional deficits and anemia were highly prevalent among readmitted patients, affecting 69.4% and 65.3%, respectively. No statistically significant association was found between early readmission and gender, place of residence, or socioeconomic status. Conclusion: Older age, chronic medical conditions, cognitive impairment, malnutrition, and anemia are key predictors of early emergency department readmission. Targeted discharge planning, nutritional assessment, and structured post-discharge follow-up may reduce preventable emergency returns and improve patient outcomes.